2020
DOI: 10.3390/biom10060859
|View full text |Cite
|
Sign up to set email alerts
|

LOMIX, a Mixture of Flaxseed Linusorbs, Exerts Anti-Inflammatory Effects through Src and Syk in the NF-κB Pathway

Abstract: Although flax (Linum usitatissimum L.) has long been used as Ayurvedic medicine, its anti-inflammatory role is still unclear. Therefore, we aimed to investigate the anti-inflammatory role of a linusorb mixture (LOMIX) recovered from flaxseed oil. Effects of LOMIX on inflammation and its mechanism of action were examined using several in vitro assays (i.e., NO production, real-time PCR analysis, luciferase-reporter assay, Western blot analysis, and kinase assay) and in vivo analysis with animal inflammation mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 42 publications
(64 reference statements)
0
13
0
Order By: Relevance
“…LOs are small biologically active cyclic peptides found in flaxseed oil, and many types of LOs have been identified and named based on their structures [ 35 ]. Of LOs, LOB3 ( Figure 1 A, molecular weight: 1040.34) and its analogs have been demonstrated to play pivotal roles in antioxidative [ 31 ] and anti-inflammatory actions [ 20 ]. Interestingly, recent studies have reported the cytotoxic effect of LOB3 on cancer cells [ 29 , 34 , 36 ]; however, the anti-cancer effect of LOB3 and the underlying mechanisms are poorly understood.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…LOs are small biologically active cyclic peptides found in flaxseed oil, and many types of LOs have been identified and named based on their structures [ 35 ]. Of LOs, LOB3 ( Figure 1 A, molecular weight: 1040.34) and its analogs have been demonstrated to play pivotal roles in antioxidative [ 31 ] and anti-inflammatory actions [ 20 ]. Interestingly, recent studies have reported the cytotoxic effect of LOB3 on cancer cells [ 29 , 34 , 36 ]; however, the anti-cancer effect of LOB3 and the underlying mechanisms are poorly understood.…”
Section: Resultsmentioning
confidence: 99%
“…Flaxseed contains 20–25% proteins and 40–45% fatty acids, including the major bioactive ingredients, such as polyunsaturated fatty acids, short-chain omega-3, lignan, mucilage, and linusorbs (LOs) [ 13 ]. Flaxseed has been consumed as a dietary supplement for human health and herbal medicines with the purpose of ameliorating many human diseases, including cardiovascular diseases, hypertension, renal disease, cancers, diabetes, stroke, skin disease, gastrointestinal disease, and inflammatory diseases [ 11 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Flaxseed has been also used for extracting flaxseed oil that is the oldest commercial oil for foods and pharmaceutical purposes, and flaxseed oil contains many bioactive ingredients such as omega-3 fatty acids, alpha-linolenic acid, lignan secoisolariciresinol diglucoside, and LOs [ 11 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations